Effect of current density on the solid electrolyte interphase formation at the lithium∣Li6PS5Cl interface - Narayanan, S; Ulissi, U; Gibson, JS; Chart, YA; Weatherup, RS; Pasta, M (Springer Nature, 2022)
Understanding the chemical composition and morphological evolution of the solid electrolyte interphase (SEI) formed at the interface between the lithium metal electrode and an inorganic solid-state electrolyte is crucial for developing reliable all-solid-state lithium batteries. To better understand the interaction between these cell components, we carry out X-ray photoemission spectroscopy (XPS) measurements during lithium plating on the surface of a Li6PS5Cl solid-state electrolyte pellet using an electron beam. The analyses of the XPS data highlight the role of Li plating current density on the evolution of a uniform and ionically conductive (i.e., Li3P-rich) SEI capable of decreasing the electrode∣solid electrolyte interfacial resistance. The XPS findings are validated via electrochemical impedance spectrsocopy measurements of all-solid-state lithium-based cells.